A novel distributed node searching method in DTNs. (2018) - Deng, Yiqin; Zhao, Ming; Wu, Zhengjiang; Xiao, Longhua
Among conventional target tracking methods in delay-tolerant networks (DTNs), there exists a type of distributed approach which is efficient with regard to target tracking. However, some nodes in these methods consume energy too quickly, resulting in energy holes and a short network lifetime. Based on the above, this research developed a novel target track strategy (MAtracking), on the basis of a mobile anchor (MA) and any correlation between nodes. It improves the effect of the target tracking through two new mechanisms: first, a new data collection method (MA), is adopted. Secondly, the correlation between nodes is used to track the target in the absence of valid mobile information about it. A large number of experimental results from real data simulations show that the proposed MAtracking method can improve the network lifetime and tracking efficiency compared with existing approaches.